GENDER BARRIERS AND OPPORTUNITIES ALONG THE NEWCASTLE DISEASE VACCINE VALUE CHAIN IN MACHAKOS TOWN SUB-COUNTY, KENYA - Faduma Abdullahi Abdirahman; Raphael Githaiga Wahome; Catherine Kaluwa; Jemimah Oduma; Jynette Jynette Nkatha; Angella Adhiambo; Kitoga Byalungwa Kyotos; Brigitte Bagnol; Marieke Rosenbaum; Janetrix Hellen Amuguni (Tropical and Subtropical Agroecosystems, 2023)
Background. Traditionally, poultry is kept and reared by women in extensive production systems. In Kenya and most developing countries, smallholder poultry productivity is constrained by diseases such as Newcastle disease (ND), which is preventable via a vaccine, yet contributes to significant morbidity and mortality among flocks primarily owned and managed by women in villages. Objective. This study aimed to map the Newcastle disease vaccine value chain stakeholders and identify the barriers and opportunities for women's engagement along the Newcastle disease vaccine value chain. Methodology. Qualitative data were collected with 15 key informant interviews and four focus group discussions with a total of 42 poultry farmers in Machakos Town sub-county, Kenya. Results. The majority of the vaccine value chain consumers were women, and limited information was one of the root causes for not vaccinating their chickens. Vaccines were considered expensive and difficult to access as the production areas were remote from the agrovet shops that retail vaccines. Implication. The study showed that women farmers had no financial control to enable vaccine procurement. Conclusion. Based on the results the government using the Extension service providers should train smallholder farmers on how to use the ND vaccine. Furthermore, manufacturers of thermo-stable ND vaccines should furnish Agrovet shops with data to enable its adoption in remote areas where the cold chain is unreliable.